Chimerism-based tolerance in organ transplantation: preclinical and clinical studies. (20th April 2017) - Oura, T; Cosimi, A B; Kawai, T
Summary: Induction of allograft tolerance has been considered the ultimate goal in organ transplantation. Although numerous protocols to induce allograft tolerance have been reported in mice, a chimerism-based approach through donor haematopoietic stem cell transplantation has been the only approach to date that induced allograft tolerance reproducibly following kidney transplantation in man. Renal allograft tolerance has been achieved by induction of either transient mixed chimerism or persistent full donor chimerism. Although the risk of rejection may be low in tolerance achieved via durable full donor chimerism, the development of graft- versus -host disease (GVHD) has limited the wider clinical application of this approach. In contrast, tolerance induced by transient mixed chimerism has not been associated with GVHD, but the risk of allograft rejection is more difficult to predict after the disappearance of haematopoietic chimerism. Current efforts are directed towards the development of more clinically feasible and reliable approaches to induce more durable mixed chimerism in order to widen the clinical applicability of these treatment regimens. Graphical Abstract: